Обзор родов Triteleia и Calliscelio (Proctotrupoidea, Scelionidae) - Козлов, М.А.; Кононова, С.В. (Вестник зоологии, 1985)
Paper contains concise morphological description of the genera mentioned and a key to all species considered. Five species are described as new, Calliscelio ruficollis Szelény for the first time is recorded within the USSR territory. Triteleia minoria sp. n.-type locality: Primorsky Krai, Pogranichny reg., Novo-Kachalinsk; T. minor sp. n.- type locality: Primorsky Krai, Vladivostok; T. persimilis sp. n.-type locality: Japan, Honshu, Inuyama; Calliscelio mirabilis sp. n. type locality: Primorsky Krai, Pogranichny reg., Barabash-Levada; C. urania sp. n.-type locality: Primorsky Krai, Khanka reg., Novo-Kachalinsk.